Prediction and detection in change of cognitive load for VIP’s by a machine learning approach - Rahman, Fahim; Ahmed, Md.Istiyak; Saad, Saif Shahnewaz; Ashrafuzzaman, Md; Mogno, Sharita Shehnaz (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.